A Novel Closed-Head Model of Mild Traumatic Brain Injury Caused by Primary Overpressure Blast to the Cranium Produces Sustained Emotional Deficits in Mice - Heldt, Scott A.; Elberger, Andrea J.; Deng, Yunping; Guley, Natalie H.; Del Mar, Nobel; Rogers, Joshua; Choi, Gy Won; Ferrell, Jessica; Rex, Tonia S.; Honig, Marcia G.; Reiner, Anton (Frontiers in Neurology, 2014)
Emotional disorders are a common outcome from mild traumatic brain injury (TBI) in humans, but their pathophysiological basis is poorly understood. We have developed a mouse model of closed-head blast injury using an air pressure wave delivered to a small area on one side of the cranium, to create mild TBI. We found that 20-psi blasts in 3-month-old C57BL/6 male mice yielded no obvious behavioral or histological evidence of brain injury, while 25–40 psi blasts produced transient anxiety in an open field arena but little histological evidence of brain damage. By contrast, 50–60 psi blasts resulted in anxiety-like behavior in an open field arena that became more evident with time after blast. In additional behavioral tests conducted 2–8 weeks after blast, 50–60 psi mice also demonstrated increased acoustic startle, perseverance of learned fear, and enhanced contextual fear, as well as depression-like behavior and diminished prepulse inhibition. We found no evident cerebral pathology, but did observe scattered axonal degeneration in brain sections from 50 to 60 psi mice 3–8 weeks after blast. Thus, the TBI caused by single 50–60 psi blasts in mice exhibits the minimal neuronal loss coupled to “diffuse” axonal injury characteristic of human mild TBI. A reduction in the abundance of a subpopulation of excitatory projection neurons in basolateral amygdala enriched in Thy1 was, however, observed. The reported link of this neuronal population to fear suppression suggests their damage by mild TBI may contribute to the heightened anxiety and fearfulness observed after blast in our mice. Our overpressure air blast model of concussion in mice will enable further studies of the mechanisms underlying the diverse emotional deficits seen after mild TBI.